Characteristics and sources of anthropogenic and biogenic hydrocarbons in sediments from the coast of Qatar. Issue 1 (15th November 2017) - Rushdi, Ahmed I.; Al-Shaikh, Ismail; El-Mubarak, Aarif H.; Alnaimi, Hajer A.J.A.; Al-Shamary, Noora; Hassan, Hassan M.; Assali, Mazen Abou
Abstract: Surface sediment samples from the coastal zone of Qatar were collected and analyzed to determine the characteristics, and sources of anthropogenic and biogenic hydrocarbons. The main compounds in these surface sediments includedn -alkanes, methyln -alkanoates, diterpenoids, hopanes, steranes, phthalate esters, polycyclic aromatic hydrocarbons (PAHs) and unresolved complex mixture (UCM). Their total concentrations ranged from 18.7 ± 3.7–81.1 ± 7.5 ng/g (3.7 ± 0.6–10.4 ± 4.8%) forn -alkanes, 8.3 ± 2.3–51 ± 3.4 ng/g (3.0 ± 2.0–5.6 ± 2.0%) for methyln -alkanoates, 1.8 ± 0.1–10.5 ± 1.0 ng/g (1.0 ± 0.5–0.4 ± 0.1%) for diterpenoids, 0.0–79.3 ± 7.4 ng/g (0.0–7.9 ± 0.6%) for hopanes, 0.0–32.9 ± 7.9 ng/g (0.0–6.5 ± 1.0%) for steranes, 0.7 ± 0.1–36.3 ± 3.4 ng/g (0.1 ± 0.1–1.9 ± 3.4%) for phthalates, 0.30 ± 0.2–7.8 ± 0.7 ng/g (0.02 ± 0.04–0.42 ± 0.72%) for PAHs, and 38 ± 9–609 ± 57 ng/g (38.5 ± 13.4–56.5 ± 13.4%) for UCM. The major sources of these lipids were anthropogenic petroleum residues and plasticizers (80–89%), with lesser amounts from natural higher plants and microbial residues (11–20%). Petroleum residues and plasticizer inputs to the coastal sediments of Qatar likely affect the marine ecosystems and associated species groups as well as shallow coastal nursery and spawning areas. Graphical abstract: Highlights: No study has investigated the characteristics/sources of extractable organic matter in sediments from the coast of Qatar. Multi-biomarker approach was used to distinguish the different sources of lipid compounds. The results showed that anthropogenic sources are major with lesser amount from natural inputs. The effects of petroleum residues and synthetic organic compounds on the coastal habitats of the Gulf need further study. More studies are warranted to understand the effects of oceanographic processes upon the fate of petroleum in the region.